PENGARUH LITERASI KEWIRAUSAHAAN DAN TECHNOPRENEURSHIP TERHADAP INTENSI BERWIRAUSAHA OLEH MAHASISWA JURUSAN PIPS UNIVERSITAS JAMBI - Berliana Agustina br Sinaga; Mayasari; Sahara (STKIP Subang, 2026)
This study was motivated by the relatively low entrepreneurial intention among university students despite the rapid development of digital technology, which has created various business opportunities. Students of the Social Science Education Department (PIPS) at the University of Jambi have the potential to become entrepreneurs; however, their levels of entrepreneurial literacy and understanding of technopreneurship vary. Therefore, it is important to examine the influence of entrepreneurial literacy and technopreneurship on students' entrepreneurial intentions. The purpose of this study was to determine the effect of entrepreneurial literacy and technopreneurship on the entrepreneurial intentions of students from the Social Science Education Department (PIPS), University of Jambi, Class of 2022. This research employed a quantitative approach using a survey method. The sample consisted of 167 students selected through simple random sampling. Data were collected using questionnaires and analyzed through multiple linear regression with the assistance of IBM SPSS Statistics 27. The results showed that entrepreneurial literacy had a significant effect on entrepreneurial intention, with a t-value of 2.409 > 1.654 and a significance value of 0.017 < 0.05. Technopreneurship also had a significant effect on entrepreneurial intention, with a t-value of 13.227 > 1.654 and a significance value of 0.000 < 0.05. Simultaneously, entrepreneurial literacy and technopreneurship had a significant effect on entrepreneurial intention, with an F-value of 153.401 > 3.05 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) was 0.652, indicating that both variables contributed 65.2% to students' entrepreneurial intentions, while the remaining 34.8% was influenced by other factors not examined in this study. The findings confirm that entrepreneurial literacy and technopreneurship are important factors in enhancing students' entrepreneurial intentions.